Analysis of the secondary breakdown of semiconductor materials on the basis of the nonlinear thermal conductivity equation - Andreyeva, N.V.; Virchenko, Yu.P. (Functional Materials, 2005)
On the basis of the Wagner approach in the theory of thermal breakdown of dielectrics, the analogous phenomenon in semiconductor films is analyzed. It is done without account of the stabilization effect connected with an external resistance. Formulas giving values of the fused channel diameters and the breakdown time are obtained. На основе подхода Вагнера в теории теплового пробоя диэлектриков проанализировано явление теплового пробоя полупроводниковой пленки без учета эффекта стабилизации внешним сопротивлением. Получены формулы для диаметров проплавленных каналов и времени пробоя.